Association between serum lipid and papillary thyroid cancer: a retrospective study in China - Zike Zhang; Xingyu Lan; Long You; Dongsheng Han; Hui Tang; Ying Zhao; Xiao Hu (PeerJ)
The incidence of papillary thyroid cancer (PTC) has increased drastically in recent decades. Various studies have reported a concurrent rise in PTC morbidity in the obese, implying a possible role of lipids in the pathogenesis of PTC. However, the role of serum lipids in the pathogenesis of PTC requires further investigation. This study aimed to investigate the correlation between serum lipid levels and PTC. From January 1, 2019, to December 31, 2020, 1,650 PTC and 882 control samples were enrolled for this study. PTC subjects were more likely to have higher body mass index (BMI), fasting blood glucose (FBG) levels, triglyceride (TG) levels, and decreased high-density lipoprotein cholesterol (HDL-C) when compared to controls (P < 0.05). Although age and low-density lipoprotein cholesterol (LDL-C) did not appear to change across all age groups, the PTC patients exhibited pronounced differences in terms of TG and HDL-C when compared to controls (P < 0.05) for each age group. BMI (odds ratio, OR and 95% CI 1.045 [1.002–1.089], P < 0.038), FGB (OR and 95% CI 2.543 [1.968–3.286], P < 0.001), TG (OR and 95% CI 1.267 [1.025–1.566], P < 0.001), and HDL-C (OR and 95% CI 0.422 [0.289–0.616], P < 0.001) were risk factors of PTC in the multivariate analysis of females. For males, FBG (OR and 95% CI 2.136 [1.551–2.941], P < 0.001), TG (OR and 95% CI 1.264 [1.039–1.615], P < 0.05), total cholesterol (TCH) (OR and 95% CI 0.778 [0.626–0.968], P < 0.001), and HDL-C (OR and 95% CI 0.154 [0.077–0.308], P < 0.001) were risk factors of PTC. Both in the female and male subgroups, patients with tumors > 1 cm in size and multifocality had a greater risk of lymph node metastasis (LNM) among PTC subjects (P < 0.001). The study results revealed that elevated TG and declined HDL-C were related to increased PTC risk among Chinese of both sexes.